A one-material cylindrical model to determine short- and long-term fluid-to-ground response factors of single U-tube borehole heat exchangers. (July 2020) - Naldi, Claudia; Zanchini, Enzo
Highlights: A one-material equivalent-cylinder model of a single U-tube borehole is presented. The cylinder has optimized thermal properties and radius of a heat-generating surface. The model allows determining short- and long-term fluid-to-ground response factors. The model is simple, and is accurate in the full time scale. The model reduces the computation time by 5000 times with respect to the 3D geometry. Abstract: A new cylindrical model is proposed, suitable to determine both the short-term and the long-term fluid-to-ground thermal response factor of a single U-tube borehole heat exchanger (BHE). In the model, a BHE is represented by an equivalent cylinder, with the same radius and heat capacity as the BHE. The cylinder is made of a homogeneous material and contains a heat-generating cylindrical surface with an equivalent radius, req, optimized by repeated 2D finite-element simulations. The thermal resistance of the layer between req and the BHE radius equals the BHE thermal resistance. A correlation yielding the optimized values of req is provided.